Colocalization of lymphocytes bearing gamma delta T-cell receptor and heat shock protein hsp65+ oligodendrocytes in multiple sclerosis. - Selmaj, K (1991)
The presence of T lymphocytes bearing the gamma delta T-cell receptor (TCR gamma delta) has been studied immunocyto-chemically in central nervous system (CNS) tissue from 13 patients with multiple sclerosis (MS), 4 with inflammatory non-MS CNS disorders, 6 with other neurological diseases, and 3 with nonneurologic conditions. Twenty-eight of 43 MS lesions contained TCR gamma delta cells and these were most frequently found in chronically demyelinated areas, in contrast to the previously studied CD4+, CD8+ (TCR alpha beta) population, which predominated in more active lesions. Some TCR gamma delta lymphocytes had an unusual morphology with long dendritic processes, which were sometimes interconnected forming a network. Because it is generally believed that TCR gamma delta lymphocytes function in a cytotoxic fashion in association with heat shock proteins (hsp), we examined the colocalization of TCR gamma delta cells with 65- and 70-kDa hsp (hsp65 and hsp70) in MS lesions. Hsp65 was expressed on immature oligodendrocytes at the margins of chronic lesions containing TCR gamma delta lymphocytes. The coexpression of these molecules might imply functional relationships perhaps of significance to the chronicity of the MS disease process and the failure of CNS remyelination.